Gibalna učinkovitost rekreativnih judoistov - Jerman, Patricia (Šport (Ljubljana), 2017)
The aim of this research was the analysis of movement efficiency of Slovenian recreational judoists with functional movement screen. 20 recreational judoists were tested (2 women and 18 men). They were split into two groups, those who had trained judo for more than two years, and those who had trained for less than two years. Each group consisted of 10 subjects. The final average mark of FMS tests of the judoists who had trained for over two years was 17.90 points (+- 2.03), 2.40 points higher than the mark of those who had trained for less than two years (15.50, +- 3.31), and it also has statistical significance; p=0.049.The paired samples t-test showed characteristic statistical difference in asymmetry in one of the five tests that are carried out with the left and right extremities, namely in the shoulder mobility test in recreationals who had trained for less than two years; p=0.04. Other asymmetry tests did not show statistically significant differences between the left and right side of the body. Based on the results, it can be concluded that training judo recreationally for over two years positively influences movement efficiency of individuals and does not cause additional asymmetries.
Keywords: asimetrija; asymmetry; FMS; gibalna učinkovitost; judo; movement efficiency; recreationals; rekreacija; sport; šport